Benign Paroxysmal Positional Vertigo; a Comparison between Particle Reposition Maneuver (Modified Epley›s Maneuver) and Medical Therapy - Arsalan Awlla Mustafa Shem; Basil Mohammed Nather Saeed; Tahir Islam Mohammed (Advanced Medical Journal)
Background and objectives: paroxysmal positional vertigo is the most common disorder causing dizziness.Most of the studies confirm the effectiveness of particle reposition maneuver in the management of benign paroxys- mal positional vertigo but still many otologists recommending medical therapy for this disorder; therefore this study has been conducted to evaluate the effect of particle reposition maneuver versus medical therapy by Betahistine-HCl for treatment of benign paroxysmal positional vertigo.